2009
DOI: 10.1002/tox.20522
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of microcystin‐producing cyanobacteria in Ugandan freshwater habitats

Abstract: Microcystins (MCs) are cyclic heptapeptides that are the most abundant toxins produced by cyanobacteria in freshwater. The phytoplankton of many freshwater lakes in Eastern Africa is dominated by cyanobacteria. Less is known, however, on the occurrence of MC producers and the production of MCs. Twelve Ugandan freshwater habitats ranging from mesotrophic to hypertrophic conditions were sampled in In order to identify the MC-producing organism in the water samples (i), the conserved aminotransferase domain part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
68
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 37 publications
12
68
0
Order By: Relevance
“…For all of the study lakes included in the current study (with the exception of Lake Nkuruba), Okello et al (2010) observed a strong positive relationship between MC cell quota and the proportion of the mcyB genotype in the Microcystis population. As such, it is likely that much of the difference in cell quota between sites may be attributable to differences in the genotypic composition of Microcystis (and the resulting capacity for MC production).…”
Section: (P Deficiency)mentioning
confidence: 47%
See 3 more Smart Citations
“…For all of the study lakes included in the current study (with the exception of Lake Nkuruba), Okello et al (2010) observed a strong positive relationship between MC cell quota and the proportion of the mcyB genotype in the Microcystis population. As such, it is likely that much of the difference in cell quota between sites may be attributable to differences in the genotypic composition of Microcystis (and the resulting capacity for MC production).…”
Section: (P Deficiency)mentioning
confidence: 47%
“…There is also evidence that buoyancy-regulating cyanobacteria can access CO 2 by rising to surface waters (Paerl 1988). Based on Okello and Kurmayer (2011), pH in our study lakes is often above 8 or even 9, suggesting that CO 2 availability is quite low. Furthermore, phytoplankton from many of these lakes (particularly where cyanobacterial biomasses were high) were strongly 13 C enriched, which indicates reduced isotopic discrimination during photosynthesis under CO 2 -limited conditions as well as possible cyanobacterial use of bicarbonate as a C source.…”
Section: (P Deficiency)mentioning
confidence: 57%
See 2 more Smart Citations
“…In addition to PCR, other molecular methods that have been employed in the past to detect and discriminate between toxic cyanobacteria using mcy genes include Southern hybridisation, dot blot hybridisation, denaturing gradient gel electrophoresis (DGGE), restriction fragment length polymorphism (RFLP), cloning and sequencing (Dittmann & Bo¨rner 2005;Kim et al 2010;Okello et al 2009). In the absence of other genera-specific primers (apart from Microcystis and Anabaena), some of these procedures (e.g.…”
Section: The 16s Rrna and Mcye Gene Targetsmentioning
confidence: 99%